2021
DOI: 10.33087/ekonomis.v5i1.199
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Internal dan Eksternal Perusahaan terhadap Nilai Perusahaan pada Perusahaan Properti dan Real Estate

Abstract: This study aims to test and analyze the influence of leverage, liquidity, inflation, and interest rates on the value of the company. Property and real estate companies listed on the Indonesia Stock Exchange in 2016-2019 as a population. Purposive sampling method for sampling and research is quantitative type. The data sources used secondary data are obtained from annual financial statements and analysis used multiple linear regressions. The results of research into external factors of the company namely inflat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
3
2
0
Order By: Relevance
“…The results of hypothesis testing show that external factors have no effect on firm value, thus the fourth hypothesis is rejected. These results support the findings of many previous researchers who believe that several macroeconomic variables such as high inflation rates [24], high interest rates Nuryani et al [27] and high exchange rate fluctuations [28] causes firms to experience financial difficulties which can reduce financial performance, so that it will have an impact on decreasing the value of the firm. From the point of view of signaling theory, sometimes asymmetric information delivery occurs, actions by management in conveying information to investors which in turn can change investors' decisions in seeing the condition of the firm [42].…”
Section: External Factors On Firm Valuesupporting
confidence: 90%
See 1 more Smart Citation
“…The results of hypothesis testing show that external factors have no effect on firm value, thus the fourth hypothesis is rejected. These results support the findings of many previous researchers who believe that several macroeconomic variables such as high inflation rates [24], high interest rates Nuryani et al [27] and high exchange rate fluctuations [28] causes firms to experience financial difficulties which can reduce financial performance, so that it will have an impact on decreasing the value of the firm. From the point of view of signaling theory, sometimes asymmetric information delivery occurs, actions by management in conveying information to investors which in turn can change investors' decisions in seeing the condition of the firm [42].…”
Section: External Factors On Firm Valuesupporting
confidence: 90%
“…So, the third hypothesis is internal factors have a significant effect on firm value. On the external factor side, high inflation rates [24], high interest rates [27], and high exchange rate fluctuations [28], demonstrated to have no impact on company value. This is because these macroeconomic issues may produce financial challenges for businesses, which will have an effect on the firm value.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by (Rakasetya, 2013) shows the results that in mining and mining services companies an increase in inflation will positively affect company value. Similar results were also shown in research (Nuryani et al, 2021) that in property and real estate companies increased inflation had a significant effect on company value. Different results were shown in research conducted by (Hendayana & Riyanti, 2020) which found that the effect of inflation on company value was not significant.…”
Section: Introductionsupporting
confidence: 87%
“…From various previous researches that examined the influence of macroeconomic factors on company value in various industries, it showed inconsistencies. (Ningsih & Waspada, 2019) in his research found results that in property companies interest rates have a positive and significant effect on company value, these results are also in line with research (Nuryani et al, 2021) that interest rates significantly affect company value. However, research conducted by (Hendayana & Riyanti, 2020) found different results, in plantation companies for the 2012-2017 period interest rates did not significantly affect company value.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation